2014
DOI: 10.1002/hipo.22253
|View full text |Cite
|
Sign up to set email alerts
|

Grid cell spatial tuning reduced following systemic muscarinic receptor blockade

Abstract: Grid cells of the medial entorhinal cortex exhibit a periodic and stable pattern of spatial tuning that may reflect the output of a path integration system. This grid pattern has been hypothesized to serve as a spatial coordinate system for navigation and memory function. The mechanisms underlying the generation of this characteristic tuning pattern remain poorly understood. Systemic administration of the muscarinic antagonist scopolamine flattens the typically positive correlation between running speed and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 53 publications
1
50
3
1
Order By: Relevance
“…However, there was a significant decrease in slope after diazepam administration and in some recording sessions the slope was negative across running speeds. However even when this occurred, no changes in gridness or spacing were seen, despite this being predicted to be the case based on previous experimental results (Barry et al, 2007; Newman et al, 2013, 2014). This could be because the overall change in slope was actually quite small in comparison to the change that occurs in novel environment experiments (Barry et al, 2007) so even if there was a change in grid scale it might have been too small to detect.…”
Section: Discussionmentioning
confidence: 59%
“…However, there was a significant decrease in slope after diazepam administration and in some recording sessions the slope was negative across running speeds. However even when this occurred, no changes in gridness or spacing were seen, despite this being predicted to be the case based on previous experimental results (Barry et al, 2007; Newman et al, 2013, 2014). This could be because the overall change in slope was actually quite small in comparison to the change that occurs in novel environment experiments (Barry et al, 2007) so even if there was a change in grid scale it might have been too small to detect.…”
Section: Discussionmentioning
confidence: 59%
“…A change in acetylcholine levels could cause a shift in overall speed modulation (Newman et al, 2013, 2014), or could be directly involved in modulating intrinsic resonance frequency relative to running speed. Acetylcholine levels have been shown to change in running vs. stationary rats (Mizuno et al, 1991; Marrosu et al, 1995) and have been shown to change the resonance frequency of medial entorhinal neurons (Heys et al, 2010; Heys and Hasselmo, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that in contrast to a hole-board with an open field, where the rats can show significant anxiety, rats prefer the narrow tunnels (Kimchi & Terkel, 2004). Based on this assumption, some laboratories have applied a circular corridor with or without a few side-boxes containing food rewards to evaluate the exploratory activity and/or learning abilities with a video-tracking system (Nadal, Rotllaant, Marquez, & Armario, 2005;Wikenheiser, Stephens, & Redish, 2013;Wikenheiser & Redish, 2015;Wikenheiser & Redish, 2011;Monaco, Rao, Roth, & Knierim, 2014;Newman, Climer, & Hasselmo, 2014). Unfortunately, both methods may require time-consuming data collection and/or they need long training sessions, or the commercial video-tracking systems (e.g., EthoVision XT) require special softwares which can analyze precisely the behavior of the animals.…”
Section: Introductionmentioning
confidence: 99%